Lithium ion battery positive electrode material, preparation method thereof and lithium ion battery
By using MnFeNi-LDH powder and segmented calcining process, the composite material of FeNi-MnO2 and MnO2 and Li2CO3 was prepared, which solved the problem of poor cycling stability of the lithium-ion battery positive electrode material at high charge and discharge rates, and achieved good cycling stability and High rate performance.
Patent Information
- Application Number
- CN202411619002.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2024-12-31
AI Technical Summary
The existing lithium-ion battery positive electrode materials have poor cycling stability and insufficient capacity at high charge and discharge rates.
MnFeNi-LDH powder is used as the precursor, and the composite materials of FeNi-MnO2 and MnO2 and Li2CO3 are prepared by ultrasonic mixing, calcining and segmented calcining processes to form a multi-metal composite structure, and optimize the internal structure of the material and the Li ion diffusion path.
It achieves good cycle stability and high rate performance of lithium-ion batteries, and can maintain a high capacity at high charge and discharge rates.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a lithium ion battery positive electrode material and a preparation method thereof, and a lithium ion battery. Background Art
[0002] With the rapid development of science and technology, lithium-ion batteries have become an important energy solution in the fields of portable electronic devices, electric vehicles and energy storage systems due to their high energy density, long cycle life and environmental protection characteristics. The performance of lithium-ion batteries depends largely on the performance of their positive electrode materials.
[0003] The patent with publication number CN118084087B discloses a lithium nickel manganese oxide material, a preparation method thereof and a lithium ion battery, and provides a preparation method of a lithium nickel manganese oxide material, comprising the following steps: S1, a manganese salt, a metal salt containing a doping element, ammonium fluoride and urea are subjected to hydrothermal reaction to obtain a layered double hydroxide compound; S2, the layered double hydroxide compound is calcined to obtain a metal composite oxide; S3, the metal composite oxide, a nickel source and a lithium source are sintered to obtain a lithium nickel manganese oxide material. The preparation method of the lithium nickel manganese oxide material can regulate the crystal structure of the material through bulk phase doping, thereby improving the structural stability and thermal stability of the material, improving the cycle performance and rate performance of the material, and using it as a positive electrode material for lithium ion batteries is beneficial to improving the electrochemical performance of the battery.
[0004] The patent with publication number CN118054014B discloses a lithium iron manganese phosphate and its preparation method and use. The lithium iron manganese phosphate includes an inner core. From the center of the inner core to the outer surface of the inner core, the content of manganese decreases gradually, the content of iron increases gradually, and the content of phosphorus increases gradually. The outer surface of the inner core is a lithium phosphate-rich protective layer. The lithium iron manganese phosphate also includes a carbon layer covering the inner core. By forming manganese, iron and phosphorus with a gradient distribution to reduce the crystallinity of the material, the material can grow faster to effectively increase the compaction density. The phosphorus element is excessive on the outer surface of the inner core to form a lithium phosphate-rich protective layer. The lithium phosphate-rich protective layer can not only improve the conductivity, but also effectively improve the manganese dissolution problem, thereby improving the capacity and cycle performance of the lithium iron manganese phosphate.
[0005] From the above-mentioned prior art, it can be found that improving the electrochemical performance of electrode materials for lithium-ion batteries has always been a research hotspot in this field. However, the existing positive electrode materials for lithium-ion batteries still have the defect of insufficient stability, resulting in poor cycle stability of lithium-ion batteries and insufficient capacity at high charge and discharge rates. Summary of the invention
[0006] Based on this, the purpose of the present invention is to provide a lithium ion battery positive electrode material and a preparation method thereof and a lithium ion battery. The lithium ion battery positive electrode material has good stability, can achieve good cycle stability of the lithium ion battery, and can still maintain a high capacity at high charge and discharge rates.
[0007] To achieve the above object, the present invention adopts the following technical solutions: The present invention first provides a method for preparing a positive electrode material for a lithium ion battery, which comprises the following steps: S1. A mixed solution containing a manganese source, a nickel source, and an iron source is mixed with polyvinyl pyrrolidone, deionized water is added, a reducing agent is added after ultrasonic mixing, the reaction is stirred, centrifuged, washed, and dried to obtain MnFeNi-LDH powder; S2. The MnFeNi-LDH powder is calcined to obtain FeNi-MnO2; S3. The FeNi-MnO2 is mixed with MnO2 and Li2CO3 and then ball-milled, tableted and calcined, and then naturally cooled and ground to obtain a positive electrode material for a lithium-ion battery.
[0008] As a further improvement of the above scheme of the present invention, in step S1, the dosage ratio of the mixed solution, polyvinyl pyrrolidone, deionized water and reducing agent is (9-11) mL: (0.4-0.6) g: (55-65) mL: (18-22) mL.
[0009] As a further improvement of the above scheme of the present invention, in step S1, the manganese source is a manganese nitrate solution and / or a manganese sulfate solution, the nickel source is a nickel nitrate solution and / or a nickel sulfate solution, and the iron source is a ferric nitrate solution and / or a ferric sulfate solution.
[0010] As a further improvement of the above scheme of the present invention, in step S1, in the mixed solution, the volume ratio of the manganese source, the nickel source and the iron source is (9-11): (5-7): (3-5); And / or, in step S1, the concentration of the mixed solution is 0.4-0.6 mol / L.
[0011] As a further improvement of the above scheme of the present invention, in step S1, the reducing agent is a NaBH4 solution with a concentration of (0.5-1.5) g / 20 mL.
[0012] As a further improvement of the above scheme of the present invention, in step S2, the calcination is carried out in an air atmosphere at 560-600° C. for 6-8 hours, and the heating rate of the calcination is 2° C. / min.
[0013] As a further improvement of the above scheme of the present invention, in step S3, the molar ratio of FeNi-MnO2, MnO2, and Li2CO3 is 2:1:1.
[0014] As a further improvement of the above scheme of the present invention, in step S3, the calcination is carried out in an air atmosphere, the temperature is increased to 700-740°C at a heating rate of 2-4°C / min and kept at 700-740°C for 3-4h, and then the temperature is continued to be increased to 800-850°C at a heating rate of 2-4°C / min and kept at 800-850°C for 2-3h.
[0015] The present invention also provides a lithium ion battery positive electrode material, which is prepared by the above-mentioned method for preparing the lithium ion battery positive electrode material.
[0016] The present invention also provides a lithium ion battery, which comprises a positive electrode sheet, an electrolyte, a separator and a negative electrode sheet. The positive electrode sheet comprises a positive electrode material, and the positive electrode material adopts the lithium ion battery positive electrode material as described above.
[0017] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention first prepares MnFeNi-LDH powder as a precursor. The layered structure of MnFeNi-LDH is conducive to the uniform distribution and diffusion of ions in subsequent reactions, providing a good foundation for the formation of uniform and dense composite oxides; the MnFeNi-LDH powder is calcined to form FeNi-MnO2, and then FeNi-MnO2 is mixed with MnO2 and Li2CO3 and calcined to obtain a positive electrode material. The positive electrode material of the present invention has a multi-metal composite and uniform structure and can show good cycle stability. At the same time, due to the optimization of the internal structure of the material and the shortening of the Li ion diffusion path, the positive electrode material of the present invention exhibits excellent rate performance, that is, it can still maintain a high capacity at high charge and discharge rates.
[0018] 2. In the present invention, when preparing the layered MnFeNi-LDH, NaBH4 solution is used as a reducing agent. Because NaBH4 helps to form the LDH precursor, and the yield of the product of this reduction method is large.
[0019] 3. The process of the present invention of mixing FeNi-MnO2 with MnO2 and Li2CO3 and then calcining in stages, firstly, performing preliminary calcination at a relatively slow heating rate, which helps the precursor to gradually decompose and convert into the target product, and reduces the structural damage caused by too fast heating; then, performing a long-term heat preservation treatment at high temperature, which helps to further improve the crystallinity and phase purity of the product and improve the electrochemical performance of the material; in addition, the heat preservation treatment at high temperature helps to promote the lattice rearrangement and defect repair of the material, and improve the stability and cycle performance of the material. At the same time, the high temperature treatment can also promote the insertion and extraction of Li ions, and improve the rate performance of the material. DETAILED DESCRIPTION
[0020] For ease of understanding of the present invention, the present invention will be described more fully below in conjunction with specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood.
[0021] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0022] Example 1 This embodiment provides a positive electrode material for a lithium-ion battery, and a preparation method thereof includes the following three steps S1-S3.
[0023] S1. Mix a 0.5 mol / L nitrate mixture (manganese nitrate, nickel nitrate, and iron nitrate in a volume ratio of 10:6:4) and polyvinyl pyrrolidone, add deionized water, and ultrasonically treat for 17 minutes, then add a 1 g / 20 mL NaBH4 aqueous solution, stir and react for 18 hours, centrifuge and separate the product, wash and dry to obtain MnFeNi-LDH powder. The dosage ratio of the nitrate mixture, polyvinyl pyrrolidone, deionized water, and NaBH4 aqueous solution is 10 mL: 0.5 g: 60 mL: 20 mL.
[0024] S2. Place the MnFeNi-LDH powder prepared in step S1 in a muffle furnace, heat it to 580°C at a heating rate of 2°C / min in an air atmosphere, and calcine it at 580°C for 7 hours to obtain FeNi-MnO2 after calcination.
[0025] S3. The FeNi-MnO2, MnO2 and Li2CO3 prepared in step S2 are mixed in a molar ratio of 2:1:1, ball-milled at a speed of 400 r / min for 4.5 hours, pressed into tablets, and calcined in a muffle furnace. The temperature is raised to 720°C at a speed of 3°C / min in an air atmosphere, and kept at 720°C for 3.5 hours; then the temperature is continued to be raised to 825°C at a speed of 3°C / min, and kept at 825°C for 2.5 hours. After natural cooling, the tablets are ground to obtain the positive electrode material for lithium-ion batteries.
[0026] Example 2 This embodiment provides a positive electrode material for a lithium-ion battery, and a preparation method thereof includes the following three steps S1-S3.
[0027] S1. Mix a 0.4 mol / L nitrate mixture (manganese nitrate, nickel nitrate, and iron nitrate in a volume ratio of 10:7:3) and polyvinyl pyrrolidone, add deionized water, and ultrasonically treat for 15 minutes, then add a 1 g / 20 mL NaBH4 aqueous solution, stir and react for 16 hours, centrifuge and separate the product, wash and dry to obtain MnFeNi-LDH powder. The dosage ratio of the nitrate mixture, polyvinyl pyrrolidone, deionized water, and NaBH4 aqueous solution is 10 mL: 0.5 g: 55 mL: 18 mL.
[0028] S2. Place the MnFeNi-LDH powder prepared in step S1 in a muffle furnace, heat it to 580°C at a heating rate of 2°C / min in an air atmosphere, and calcine it at 580°C for 7 hours to obtain FeNi-MnO2 after calcination.
[0029] S3. The FeNi-MnO2, MnO2 and Li2CO3 prepared in step S2 are mixed in a molar ratio of 2:1:1, ball-milled at a speed of 350 r / min for 4 hours, pressed into tablets, and calcined in a muffle furnace. The temperature is raised to 700°C at a speed of 2°C / min in an air atmosphere, and kept at 720°C for 3 hours; then the temperature is continued to be raised to 800°C at a speed of 2°C / min, and kept at 800°C for 2 hours. After natural cooling, the tablets are ground to obtain the positive electrode material for lithium-ion batteries.
[0030] Example 3 This embodiment provides a positive electrode material for a lithium-ion battery, and a preparation method thereof includes the following three steps S1-S3.
[0031] S1. Mix a 0.6 mol / L nitrate mixture (manganese nitrate, nickel nitrate, and iron nitrate in a volume ratio of 9:6:5) and polyvinyl pyrrolidone, add deionized water, and ultrasonically treat for 20 minutes, then add a 1 g / 20 mL NaBH4 aqueous solution, stir and react for 20 hours, centrifuge and separate the product, wash and dry to obtain MnFeNi-LDH powder. The dosage ratio of the nitrate mixture, polyvinyl pyrrolidone, deionized water, and NaBH4 aqueous solution is 10 mL: 0.6 g: 65 mL: 22 mL.
[0032] S2. Place the MnFeNi-LDH powder prepared in step S1 in a muffle furnace, heat it to 600°C at a heating rate of 2°C / min in an air atmosphere, and calcine it at 600°C for 8 hours to obtain FeNi-MnO2 after calcination.
[0033] S3. The FeNi-MnO2, MnO2 and Li2CO3 prepared in step S2 are mixed in a molar ratio of 2:1:1, ball-milled at a speed of 450 r / min for 5 hours, and calcined in a muffle furnace after tableting. The temperature is raised to 740°C at a speed of 4°C / min in an air atmosphere, and kept at 740°C for 4 hours; then the temperature is continued to be raised to 850°C at a speed of 2°C / min, and kept at 850°C for 3 hours. After natural cooling, the mixture is ground to obtain the positive electrode material for lithium-ion batteries.
[0034] Example 4 This embodiment provides a positive electrode material for a lithium-ion battery, and a preparation method thereof includes the following three steps S1-S3.
[0035] S1. Mix a 0.5 mol / L nitrate mixture (manganese nitrate, nickel nitrate, and iron nitrate mixed in a volume ratio of 10:6:4) and polyvinyl pyrrolidone, add deionized water, and ultrasonically treat for 20 minutes, then add a 1 g / 20 mL NaBH4 aqueous solution, stir and react for 20 hours, centrifuge and separate the product, wash and dry to obtain MnFeNi-LDH powder. The dosage ratio of the nitrate mixture, polyvinyl pyrrolidone, deionized water, and NaBH4 aqueous solution is 10 mL: 0.4 g: 65 mL: 18 mL.
[0036] S2. Place the MnFeNi-LDH powder prepared in step S1 in a muffle furnace, heat it to 560°C at a heating rate of 2°C / min in an air atmosphere, and calcine it at 560°C for 8 hours to obtain FeNi-MnO2 after calcination.
[0037] S3. The FeNi-MnO2, MnO2 and Li2CO3 prepared in step S2 are mixed in a molar ratio of 2:1:1, ball-milled at a speed of 350 r / min for 5 hours, pressed into tablets, and calcined in a muffle furnace. The temperature is raised to 740°C at a speed of 2°C / min in an air atmosphere, and kept at 740°C for 4 hours; then the temperature is continued to be raised to 800°C at a speed of 4°C / min, and kept at 800°C for 3 hours. After natural cooling, the tablets are ground to obtain the positive electrode material for lithium-ion batteries.
[0038] Comparative Example 1 This comparative example proposes a lithium-ion battery positive electrode material, and the preparation method thereof includes the following three steps S1-S3.
[0039] S1. Mix a 0.5 mol / L nitrate mixture (manganese nitrate, nickel nitrate, and cobalt nitrate in a volume ratio of 10:6:4) and polyvinyl pyrrolidone, add deionized water, and ultrasonically treat for 17 minutes, then add a 1 g / 20 mL NaBH4 aqueous solution, stir and react for 18 hours, centrifuge and separate the product, wash and dry to obtain MnFeNi-LDH powder. The dosage ratio of the nitrate mixture, polyvinyl pyrrolidone, deionized water, and NaBH4 aqueous solution is 10 mL: 0.5 g: 60 mL: 20 mL.
[0040] S2. Place the MnCoNi-LDH powder prepared in step S1 in a muffle furnace, heat it to 580°C at a heating rate of 2°C / min in an air atmosphere, and calcine it at 580°C for 7 hours to obtain CoNi-MnO2 after calcination.
[0041] S3. The CoNi-MnO2, MnO2 and Li2CO3 prepared in step S2 are mixed in a molar ratio of 2:1:1, ball-milled at a speed of 400 r / min for 4.5 hours, pressed into tablets, and calcined in a muffle furnace. The temperature is increased to 720°C at a rate of 3°C / min in an air atmosphere, and kept at 720°C for 3.5 hours; then the temperature is continued to be increased to 825°C at a rate of 3°C / min, and kept at 825°C for 2.5 hours. After natural cooling, the mixture is ground to obtain a positive electrode material for a lithium-ion battery.
[0042] Comparative Example 2 This comparative example proposes a lithium-ion battery positive electrode material, and the preparation method thereof includes the following three steps S1-S3.
[0043] S1. Mix a 0.5 mol / L nitrate mixture (manganese nitrate, nickel nitrate, and copper nitrate in a volume ratio of 10:6:4) and polyvinyl pyrrolidone, add deionized water, and ultrasonically treat for 17 minutes, then add a 1 g / 20 mL NaBH4 aqueous solution, stir and react for 18 hours, centrifuge and separate the product, wash and dry to obtain MnCuNi-LDH powder. The dosage ratio of the nitrate mixture, polyvinyl pyrrolidone, deionized water, and NaBH4 aqueous solution is 10 mL: 0.5 g: 60 mL: 20 mL.
[0044] S2. Place the MnCuNi-LDH powder prepared in step S1 in a muffle furnace, heat it to 580°C at a heating rate of 2°C / min in an air atmosphere, and calcine it at 580°C for 7 hours to obtain CuNi-MnO2 after calcination.
[0045] S3. The CuNi-MnO2, MnO2 and Li2CO3 prepared in step S2 are mixed in a molar ratio of 2:1:1, ball-milled at a speed of 400 r / min for 4.5 hours, pressed into tablets, and calcined in a muffle furnace. The temperature is increased to 720°C at a speed of 3°C / min in an air atmosphere, and kept at 720°C for 3.5 hours; then the temperature is continued to be increased to 825°C at a speed of 3°C / min, and kept at 825°C for 2.5 hours. After natural cooling, the mixture is ground to obtain a positive electrode material for a lithium-ion battery.
[0046] Comparative Example 3 This comparative example proposes a lithium-ion battery positive electrode material, and the preparation method thereof includes the following three steps S1-S3.
[0047] S1. Mix a 0.5 mol / L nitrate mixture (manganese nitrate and nickel nitrate mixed in a volume ratio of 10:6) and polyvinyl pyrrolidone, add deionized water, ultrasonically treat for 17 minutes, add a 1 g / 20 mL NaBH4 aqueous solution, stir and react for 18 hours, centrifuge and separate the product, wash and dry to obtain MnNi-LDH powder. The dosage ratio of the nitrate mixture, polyvinyl pyrrolidone, deionized water and NaBH4 aqueous solution is 10 mL: 0.5 g: 60 mL: 20 mL.
[0048] S2. Place the MnNi-LDH powder prepared in step S1 in a muffle furnace, heat it to 580°C at a heating rate of 2°C / min in an air atmosphere, and calcine it at 580°C for 7 hours to obtain Ni-MnO2.
[0049] S3. The Ni-MnO2, MnO2 and Li2CO3 prepared in step S2 are mixed in a molar ratio of 2:1:1, ball-milled at a speed of 400 r / min for 4.5 h, pressed into tablets, and calcined in a muffle furnace. The temperature is increased to 720°C at a speed of 3°C / min in an air atmosphere, and kept at 720°C for 3.5 h; then the temperature is continued to be increased to 825°C at a speed of 3°C / min, and kept at 825°C for 2.5 h. After natural cooling, the mixture is ground to obtain a positive electrode material for a lithium-ion battery.
[0050] Comparative Example 4 This comparative example proposes a lithium-ion battery positive electrode material, and the preparation method thereof includes the following three steps S1-S3.
[0051] S1. Mix a 0.5 mol / L nitrate mixture (manganese nitrate, nickel nitrate, and iron nitrate in a volume ratio of 10:6:4) and polyvinyl pyrrolidone, add deionized water, and ultrasonically treat for 17 minutes, then add a 1 g / 20 mL NaBH4 aqueous solution, stir and react for 18 hours, centrifuge and separate the product, wash and dry to obtain MnCuNi-LDH powder. The amount ratio of the nitrate mixture, polyvinyl pyrrolidone, deionized water, and NaBH4 aqueous solution is 10 mL: 0.5 g: 60 mL: 20 mL.
[0052] S2. Place the MnFeNi-LDH powder prepared in step S1 in a muffle furnace, heat it to 580°C at a heating rate of 2°C / min in an air atmosphere, and calcine it at 580°C for 7 hours to obtain FeNi-MnO2 after calcination.
[0053] S3. The FeNi-MnO2, MnO2 and Li2CO3 prepared in step S2 are mixed in a molar ratio of 2:1:1, ball-milled at a speed of 400 r / min for 4.5 h, pressed into tablets and calcined in a muffle furnace, heated to 720°C at a speed of 3°C / min in an air atmosphere, and kept at 720°C for 6 h. After natural cooling, they are ground to obtain the positive electrode material for lithium-ion batteries.
[0054] Comparative Example 5 This comparative example proposes a lithium-ion battery positive electrode material, and the preparation method thereof includes the following three steps S1-S3.
[0055] S1. Mix a 0.5 mol / L nitrate mixture (manganese nitrate, nickel nitrate, and iron nitrate in a volume ratio of 10:6:4) and polyvinyl pyrrolidone, add deionized water, and ultrasonically treat for 17 minutes, then add a 1 g / 20 mL NaBH4 aqueous solution, stir and react for 18 hours, centrifuge and separate the product, wash and dry to obtain MnNi-LDH powder. The dosage ratio of the nitrate mixture, polyvinyl pyrrolidone, deionized water, and NaBH4 aqueous solution is 10 mL: 0.5 g: 60 mL: 20 mL.
[0056] S2. Place the MnFeNi-LDH powder prepared in step S1 in a muffle furnace, heat it to 580°C at a heating rate of 2°C / min in an air atmosphere, and calcine it at 580°C for 7 hours to obtain FeNi-MnO2 after calcination.
[0057] S3. The FeNi-MnO2, MnO2 and Li2CO3 prepared in step S2 are mixed in a molar ratio of 2:1:1, ball-milled at a speed of 400 r / min for 4.5 h, pressed into tablets and calcined in a muffle furnace, heated to 825°C at a speed of 3°C / min in an air atmosphere, and kept at 825°C for 6 h. After natural cooling, they are ground to obtain the positive electrode material for lithium-ion batteries.
[0058] Comparative Example 6 This comparative example proposes a lithium-ion battery positive electrode material, and the preparation method thereof includes the following three steps S1-S3.
[0059] S1. Dissolve 0.5 mol of MnSO4·H2O, 0.3 mol of Fe(NO3)3·9H2O, 0.2 mol of NiNO3, 4 mol of NH4F, and 10 mol of urea in 200 mL of deionized water, and stir at room temperature to form a uniform solution; then pour it into the lining of a stainless steel reactor, place it in a 120°C oven for hydrothermal reaction for 6 hours; after the reaction is completed and cooled to room temperature, collect the precipitate by centrifugation, wash it twice with deionized water and ethanol in turn, and then dry it to obtain MnFeNi-LDH powder; S2. The prepared MnFeNi-LDH powder was placed in a muffle furnace, the heating rate was 2°C / min, and the calcination conditions were calcined at 580°C for 7h in an air atmosphere to obtain FeNi-MnO2; S3. The FeNi-MnO2, MnO2 and Li2CO3 prepared in step S2 are mixed in a molar ratio of 2:1:1, ball-milled at a speed of 400 r / min for 4.5 h, pressed into tablets, and calcined in a muffle furnace. The temperature is raised to 720°C at a speed of 3°C / min in an air atmosphere, and kept at 720°C for 3.5 h. Subsequently, the temperature is continued to be raised to 825°C at a speed of 3°C / min, and kept at 825°C for 2.5 h. After natural cooling, the tablets are ground to obtain the positive electrode material for lithium-ion batteries.
[0060] Test Case A button cell was prepared using the positive electrode materials for lithium ion batteries prepared in the above-mentioned embodiments 1-4 and comparative examples 1-5: a mixture of the positive electrode material for lithium ion batteries, acetylene black and polyvinylidene fluoride was uniformly mixed in a mass ratio of 82:10:8, 0.5 g of the mixture was taken and fully mixed with 0.1 g of N-methylpyrrolidone to form a uniform slurry, which was coated on an aluminum foil and dried to form a positive electrode sheet; a metal lithium sheet was used as the negative electrode; the diaphragm was an imported polypropylene microporous membrane (Celgard2400); the electrolyte was an equal mixture of 1 mol / L LiPF6, ethylene carbonate (EC) and dimethyl carbonate (DMC), and the cells were assembled into a 2025 button cell in an argon-filled glove box.
[0061] The button cells prepared above were subjected to electrochemical tests in a battery testing system: (1) Cyclic performance test: voltage range 3~4.9V (vs.Li + / Li), cycle performance test at room temperature under 0.5C (1C=147mAh / g); (2) rate performance test: charge and discharge for 3 cycles at 0.5C charge rate and 2C discharge rate; charge and discharge for 3 cycles at 0.5C charge rate and 4C discharge rate. The electrochemical performance test results are shown in Table 1.
[0062] Table 1 Electrochemical performance test results
[0063] From the results in Table 1, we can see that: Compared with the manganese, nickel, cobalt / copper metal composite positive electrode materials prepared in Comparative Examples 1-2, the manganese, nickel, iron metal composite positive electrode materials prepared in Examples 1-4 have higher capacity retention rates after 100 and 200 cycles at 0.5C, and have higher capacity retention rates at 2C and 4C discharge rates; it proves that the manganese, nickel, iron metal composite positive electrode materials prepared in the present application have good cycle stability and can still maintain a high capacity at high charge and discharge rates; Compared with the manganese and nickel metal composite positive electrode material prepared in Comparative Example 3, the manganese, nickel and iron metal composite positive electrode material prepared in Examples 1-4 has a higher capacity retention rate after 100 and 200 cycles at 0.5C, and has a higher capacity retention rate at 2C and 4C discharge rates; it proves that the manganese, nickel and iron metal composite positive electrode material prepared in the present application has good cycle stability and can still maintain a high capacity at a high charge and discharge rate; Compared with the manganese, nickel, and iron metal composite positive electrode materials prepared in Comparative Examples 4-5, the manganese, nickel, and iron metal composite positive electrode materials prepared in Examples 1-4 have higher capacity retention rates after 100 and 200 cycles at 0.5C, and have higher capacity retention rates at 2C and 4C discharge rates; it proves that the positive electrode material prepared by the staged calcination process in the present application has good cycle stability and can still maintain a high capacity at high charge and discharge rates; Compared with the manganese, nickel and iron metal composite positive electrode material prepared in Comparative Example 6, the manganese, nickel and iron metal composite positive electrode material prepared in Examples 1-4 has a higher capacity retention rate after cycling 100 and 200 cycles at 0.5C, and has a higher capacity retention rate at 2C and 4C discharge rates; it is proved that the layered structure MnFeNi-LDH powder prepared by the method of the present application is used as a precursor, which is beneficial to the uniform distribution and diffusion of ions in subsequent reactions, and provides a good foundation for the formation of uniform and dense composite oxides.
[0064] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0065] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a positive electrode material for a lithium ion battery, characterized in that: It includes the following steps: S1. The mixed solution obtained by mixing the manganese source, the nickel source and the iron source was mixed with polyvinyl pyrrolidone, deionized water was added, and a reducing agent was added after ultrasonic mixing, the reaction was stirred, centrifuged, washed and dried to obtain MnFeNi-LDH powder; S2. The MnFeNi-LDH powder is calcined to obtain FeNi-MnO2; S3. The FeNi-MnO2 is mixed with MnO2 and Li2CO3 and then ball-milled, tableted and calcined, and then naturally cooled and ground to obtain a positive electrode material for a lithium-ion battery.
2. The method for preparing a positive electrode material for a lithium ion battery according to claim 1, characterized in that: In step S1, the ratio of the mixed solution, polyvinyl pyrrolidone, deionized water and reducing agent is (9-11) mL: (0.4-0.6) g: (55-65) mL: (18-22) mL.
3. The method for preparing a positive electrode material for a lithium ion battery according to claim 1, characterized in that: In step S1, the manganese source is a manganese nitrate solution and / or a manganese sulfate solution, the nickel source is a nickel nitrate solution and / or a nickel sulfate solution, and the iron source is a ferric nitrate solution and / or a ferric sulfate solution.
4. The method for preparing a positive electrode material for a lithium ion battery according to claim 1, characterized in that: In step S1, in the mixed solution, the volume ratio of the manganese source, the nickel source and the iron source is (9-11): (5-7): (3-5); And / or, in step S1, the concentration of the mixed solution is 0.4-0.6 mol / L.
5. The method for preparing a positive electrode material for a lithium ion battery according to claim 1, characterized in that: In step S1, the reducing agent is a NaBH4 solution with a concentration of (0.5-1.5) g / 20 mL.
6. The method for preparing a positive electrode material for a lithium ion battery according to claim 1, characterized in that: In step S2, the calcination is carried out in an air atmosphere, with the temperature being raised to 560-600°C at a heating rate of 2-4°C / min and calcined at 560-600°C for 6-8h.
7. The method for preparing a positive electrode material for a lithium ion battery according to claim 1, characterized in that: In step S3, the molar ratio of FeNi-MnO2, MnO2, and Li2CO3 is 2:1:1; And / or, in step S3, the ball milling is performed in a ball mill at a rotation speed of 350-450 r / min for 4-5 h.
8. The method for preparing a positive electrode material for a lithium ion battery according to claim 1, characterized in that: In step S3, the calcination is carried out in an air atmosphere, heating to 700-740°C at a heating rate of 2-4°C / min and keeping at 700-740°C for 3-4h, then continuing to heat to 800-850°C at a heating rate of 2-4°C / min and keeping at 800-850°C for 2-3h.
9. A positive electrode material for a lithium ion battery, characterized in that: The positive electrode material is prepared by the method for preparing a positive electrode material for a lithium ion battery as claimed in any one of claims 1 to 8.
10. A lithium ion battery comprising a positive electrode sheet, an electrolyte, a separator and a negative electrode sheet, wherein the positive electrode sheet comprises a positive electrode material, characterized in that: The positive electrode material is the lithium-ion battery positive electrode material as claimed in claim 9.
